A 5-year randomized controlled study of learning, problem solving ability, and quality of life modifications in people with type 2 diabetes managed by group care. - Trento M; Passera P; Borgo E; Tomalino M; Bajardi M; Cavallo F; Porta M; Trento, Marina; Passera, Pietro; Borgo, Enrica; Tomalino, Marco; Bajardi, Marina; et al. (Diabetes Care, 2004)
Objective: To study time course changes in knowledge, problem solving ability, and quality of life in patients with type 2 diabetes managed by group compared with individual care and education.Research Design and Methods: We conducted a 5-year randomized controlled clinical trial of continuing systemic education delivered by group versus individual diabetes care in a hospital-based secondary care diabetes unit. There were 120 patients with non-insulin-treated type 2 diabetes enrolled and randomly allocated to group or individual care. Eight did not start and 28 did not complete the study. The main outcome measures were knowledge of diabetes, problem solving ability, quality of life, HbA1c, BMI, and HDL cholesterol.Results: Knowledge of diabetes and problem solving ability improved from year 1 with group care and worsened among control subjects (P<0.001 for both). Quality of life improved from year 2 with group care but worsened with individual care (P<0.001). HbA1c level progressively increased over 5 years among control subjects (+1.7%, 95% CI 1.1-2.2) but not group care patients (+0.1%, -0.5 to 0.4), in whom BMI decreased (-1.4, -2.0 to -0.7) and HDL cholesterol increased (+0.14 mmol/l, 0.07-0.22).Conclusions: Adults with type 2 diabetes can acquire specific knowledge and conscious behaviors if exposed to educational procedures and settings tailored to their needs. Traditional one-to-one care, although delivered according to optimized criteria, is associated with progressive deterioration of knowledge, problem solving ability, and quality of life. Better cognitive and psychosocial results are associated with more favorable clinical outcomes.